2010
DOI: 10.5194/acp-10-2561-2010
|View full text |Cite
|
Sign up to set email alerts
|

Applying an ensemble Kalman filter to the assimilation of AERONET observations in a global aerosol transport model

Abstract: Abstract. We present a global aerosol assimilation system based on an Ensemble Kalman filter, which we believe leads to a significant improvement in aerosol fields. The ensemble allows realistic, spatially and temporally variable model covariances (unlike other assimilation schemes). As the analyzed variables are mixing ratios (prognostic variables of the aerosol transport model), there is no need for the extra assumptions required by previous assimilation schemes analyzing aerosol optical thickness (AOT).We d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 33 publications
3
97
0
Order By: Relevance
“…The impact of the AOD assimilation on the model found in our study is coherent with findings of other studies (Zhang et al, 2008;Schutgens et al, 2010;Liu et al, 2011). Our approach is the most similar to the approach used by Benedetti et al (2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The impact of the AOD assimilation on the model found in our study is coherent with findings of other studies (Zhang et al, 2008;Schutgens et al, 2010;Liu et al, 2011). Our approach is the most similar to the approach used by Benedetti et al (2009).…”
Section: Discussionsupporting
confidence: 82%
“…Benedetti et al (2009) described the assimilation of AOD in the European Centre for Medium-Range Weather Forecasts (ECMWF) Integrated Forecasting System (IFS) using the 4-D-VAR method, while Yumimoto et al (2008) used the same approach to assimilate satellite lidar profiles in the RAMS/CFORS-4-D-VAR (RC4) model. Sequential assimilation approaches are also documented: optimal interpolation used by, for example, Collins et al (2001) and Rasch et al (2001) in the Model of Atmospheric Transport and Chemist (MATCH) and (Tombette et al, 2009) in the Polyphemus system; or the ensemble Kalman filter used by, for example, Sekiyama et al (2010) in the Model of Aerosol Species in the Global Atmosphere (MASINGAR), Schutgens et al (2010) in the SPRINTARS model, Pagowski and Grell (2012) in the WRF-Chem model, Dai et al (2014) in the Non-hydrostatic ICosahedral Atmospheric Model (NICAM) and Rubin et al (2016) in the Ensemble Navy Aerosol Analysis Prediction System/Data Assimilation Research Testbed (ENAAPS-DART) system.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have shown notable improvements in aerosol forecasting through the assimilation of satellite aerosol products, mostly from daytime observations (e.g., Zhang et al, 2008aZhang et al, , 2011Zhang et al, , 2014Yumimoto et al, 2008;Uno et al, 2008;Benedetti et al, 2009;Schutgens et al, 2010;Sekiyama et al, 2010). To capture the diurnal cycle, the aerosol modeling community requires nighttime satellite aerosol data hav-ing broad spatial coverage and high temporal resolution to further advance aerosol, visibility, and air quality forecasts (e.g., Zhang et al, 2011Zhang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Rank histograms are generated by repeatedly tallying the rank of the observation relative to values from the ensemble sorted from lowest to highest and can be used for diagnosing errors in the mean and spread of the ensemble forecast (Hamill, 2001). In order to account for the effect of observation error in the rank histograms, the forecast values are randomly perturbed for each ensemble member by the observation error (Anderson, 1996,;Hamill, 2001;Saetra et al, 2004). The focus of this observation-space evaluation relative to MODIS AOT is on the prior since this is a stronger indicator of how the assimilation is impacting the model forecast.…”
Section: Dart Eakf Implementation and Optimizationmentioning
confidence: 99%